American Immigration After 1996 : The Shifting Ground of Political Inclusion - Arnold, Kathleen R., 1966- (Book collections on Project MUSE., 2011)
"Examines the underlying complexities of immigration in the United States and the relationship between globalization of the economy and issues of political sovereignty"--Provided by publisher.